The Feature of Distribution and Clonality of TCR γ/δ Subfamilies T Cells in Patients with B-Cell Non-Hodgkin Lymphoma - Liang Wang; Meng Xu; Chunyan Wang; Lihua Zhu; Junyan Hu; Shaohua Chen; Xiuli Wu; Bo Li; Yangqiu Li (Journal of Immunology Research)
Restricted T-cell receptor (TCR) Vα/Vβ repertoire expression and clonal expansion of αβ T cells especially for putative tumor-associated antigens were observed in patients with hematological malignancies. To further characterize the γδ T-cell immune status in B-cell non-Hodgkin lymphoma (B-NHL), we investigated the distribution and clonality of TCR Vγ/Vδ repertoire in peripheral blood (PB), bone marrow (BM), and lymph node (LN) from patients with B-NHL. Four newly diagnosed B-NHL cases, including three with diffuse large B-cell lymphoma (DLBCL) and one with small lymphocytic lymphoma (SLL), were enrolled. The restrictive expression of TCR Vγ/Vδ subfamilies with different distribution patterns could be detected in PB, BM, or LN from all of four patients, and partial subfamily T cells showed clonal proliferation. At least one clonally expanded Vδ subfamily member was found in PB from each patient. However, the expression pattern and clonality of TCR Vγ/Vδ changed in different immune organs and showed individual feature in different patients. The clonally expanded Vδ5, Vδ6, and Vδ8 were detected only in PB but neither in BM nor LN while clonally expanded Vδ2 and Vδ3 could be detected in both PB and BM/LN. In conclusion, the results provide a preliminary profile of distribution and clonality of TCR γ/δ subfamilies T cells in PB, BM, and LN from B-NHL; similar clonally expanded Vδ subfamily T cells in PB and BM may be related to the same B-cell lymphoma-associated antigens, while the different reactive clonally expanded Vγ/Vδ T cells may be due to local immune response.